Estudo da sailboat para sistemas binários - Pinheiro, Tiago Francisco Lins Leal [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The sailboat is a stable region of particles located between the orbits of Pluto and Charon, this region has perculiar features and were studied in detail by Winter et al. (2014) with the goal to discover what the risk this region could cause for the New Horizons's mission. The authors checked the stability of the sailboat through the Poincaré surface of scetion. To a deepier understanding of the sailboat, in this project has been created hypothetical binary systems. Setting the mass (mp) and radius (rp) of the primary body equals to Pluto. Varying the mass ratio of the system, since µ = [0.05,0.70], in the second body the radius adopted was identical to the Charon rs = 610 km and it had a circular or eccentric orbit, depending of the simulation. The separation distance (d) between two bodies was adopted the same of Pluto-Charon system. We numerically integrated the orbits using the Radau 15 (EVERHART, 1985), where it was considered that the massless particules were disturbed by the binary but it can't change the orbit of massive bodies. The time span adopted was 104 orbital periods (6500 days, the same as the binary Pluto-Charon). The results of the simulation showed that the existence of this region is limited within µ between 0.05 and 0.27, this region is initially formed beyond to 0:5d, however, it get closer to the primary body when the µ grows. When a mass ratio is between 0.28 and 0.29 two new stable regions arised, one situated beyond 0:6d and extends to a distance greater than 0:8d and another region located at approximately 0:45d, but has high eccentricity, above 0.6. With a small increase in mass ratio these two regions mixed with a sailboat, forming a single region. The simulations show that small increments in eccentricity of the secondary body cause a significant reduction in the size of ... ( Complete abstract electronic access below)

A sailboat é uma região estável de partículas localizadas entre a órbita de Plutão e Caronte. Ela possui características muito peculiares e foram estudadas minuciosamente por Winter et al. (2014) com o objetivo de descobrir quais os riscos esta região poderia trazer para a missão New Horizons. Os autores confirmaram a estabilidade da sailboat através de superfícies de seção de Poincaré. Para um entendimento mais profundo da sailboat, neste trabalho foram criados sistemas binários hipotéticos. Estabelecendo a massa (mp) e raio (rp) do corpo primário são iguais a de Plutão e variou-se a razão de massa do sistema, no intervalo µ = [0.05,0.70]. No corpo secundário o raio utilizado foi idêntico ao de Caronte rs = 610 km com órbitas circulares ou excêntrica, dependendo da simulação. Para a distância de separação dos dois corpos (d), também foi adotado a mesma do sistema Plutão-Caronte. As simulações numéricas foram feitas utilizando o integrador Radau 15 (EVERHART, 1985), onde considerou-se que as partículas (sem massas) sofrem a perturbação do binário mas não alteram a órbita dos corpos massivos. O tempo de integração adotado foi de 104 períodos orbitais (6500 dias, o mesmo da binária Plutão-Caronte). Os resultados das simulações mostraram que a existência desta região se limita a µ entre 0.05 e 0.27, esta região é formada inicialmente além de 0:5d, porém se aproxima do corpo primário a medida que µ cresce. Quando a razão de massa está entre 0.28 e 0.29 duas novas regiões estáveis surgem, uma situada além de 0:6d e se estende a distância superior a 0:8d e outra região localizada em aproximadamente 0:45d e de partículas com alta excentricidade, acima 0.6. Com um pequeno aumento na razão de massa estas duas regiões se misturam com a sailboat, formando uma única região. ...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Planetas - Órbitas; Sistema binário (Matemática); Metodos de simulação; Planets